Effect of calcium chloride and refrigeration on the quality and organoleptic characteristics of cape gooseberry (Physalis peruviana L.) - Javier Giovanni Alvarez Herrera; Andrea Johana Reyes-Medina; Elberth Hernando Pinzón (Acta Agronómica)
The gooseberry is one of the exotic fruit species most important in Colombia. Calcium has been shown to be important for quality maintenance in fruits and vegetables, as it prevents a number of physiological disorders reinforce the cell walls and stabilize cellular membranes. With the aim to increase the fruit calcium concentration, a completely randomized design with four treatments was performed: a control and three applications of CaCl2 (0.5%, 1% and 2%), with four replicates, for a total of 16 experimental units (EU). The fruit was collected at maturity stage 6 according to the standard Icontec NTC 4580, completely healthy and homogeneous. The fruit was subsequently stored at 21 ± 1 ° C (RH 45%). The application of calcium in the gooseberry fruits decreased mass loss, firmness and ATT. Calcium treated fruit showed an increase in SST. In contrast, the treatments did not affect color. The doses of CaCl2 tested delayed ripening and prevented fruit deterioration.